COMMUNICATION BETWEEN THE MEDIAN AND MUSCULOCUTANEOUS NERVE. AN ANATOMICAL STUDY - HUMBERTO FERREIRA ARQUEZ, (International Journal of Pharma and Bio Sciences, 2015)
Anatomical variations of median and musculocutaneous nerves are of interest for anatomists, surgeons, orthopaedicians, neurologists. The nerves of extremities are especially vulnerable to injury and entrapment syndromes. A total of 13 cadavers (26 embalmed arms) were used for the study. In 92,4 % of the cases the median and musculocutaneos nerves having a classic pattern of branching without communications and in 7,6% the musculocutaneous nerve fused with the median nerve almost 13,5 cm proximal to elbow joint after the emergence of lateral cutaneous branch for forearm. The communicating branch arose from the musculocutaneous nerve at a distance of 12,6 cms from the tip of coracoid process on right and left side and joined the median nerve a 16,5 cms same bony point. This variations is important to be aware while planning a surgery in the region of arm to avoid injured the nerves during operations and achieve effective nerve blockade.